Children’s’ travel to school and parents’ criteria in the school selection: Gombak district - Ibrahim, Nuraihan; Mohamed Osman, Mariana; Bachok, Syahriah (e-International Publishing House, Ltd., UK., 2018)
School is a nucleus of the society. School development should be planned based on the sustainable concept. The purpose of this paper is to determining parents’ criteria in selecting the suitable public school for their children. There are various factors underlying in determining the school selection which are location, distance, school facilities, academic school’s performance, extra-curricular and school environment. The findings showed that academic school’s performance is the most important criteria of parents in selecting school for enrolling children. Hopefully, the paper will benefit the local authority, parents as well as children in term of public school development in the community